1990
DOI: 10.2118/17149-pa
|View full text |Cite
|
Sign up to set email alerts
|

Formation Permeability Damage Induced by Completion Brines

Abstract: Summary In a laboratory study to determine permeability changes induced by floodinglarge Berea and Casper sandstone cores with NaCl and KCl brine, theconcentration of each brine was incrementally increased from 0 to 22 wt% andthen decreased from 22 to 0 wt%. In both sandstones, the permeability to KClbrines increased noticeably with increases in KCl concentration up to 1 0 wt%. Permeability remained at the higher levels throughout the remainder of eachflood until a critically low salinity lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The CSC depends strongly on the cation type within the aqueous solution. K + ‐saturated clay‐bearing sandstones show a significantly lower CSC as compared to that of Na + ‐saturated sandstones (e.g., Azari & Leimkuhler, 1990). Bivalent cations like Ca 2+ and Mg 2+ stabilize permeability down to very low salt concentrations (Gray, 1966; Khilar & Fogler, 1984; Mohan et al, 1993; Mungan, 1968).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CSC depends strongly on the cation type within the aqueous solution. K + ‐saturated clay‐bearing sandstones show a significantly lower CSC as compared to that of Na + ‐saturated sandstones (e.g., Azari & Leimkuhler, 1990). Bivalent cations like Ca 2+ and Mg 2+ stabilize permeability down to very low salt concentrations (Gray, 1966; Khilar & Fogler, 1984; Mohan et al, 1993; Mungan, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Chemically induced permeability changes in clay‐bearing sandstones related to low‐salinity fluids are well‐known (e.g., Azari & Leimkuhler, 1990; Khilar & Fogler, 1984; Kia et al, 1987; Mohan et al, 1993; Mohan & Fogler, 1997; Mungan, 1968; Omar, 1990; Rahman et al, 1995; Sharma et al, 1985; Yu et al, 2018). Generally, permeability is not reduced unless the salinity is lower than a critical salt concentration (CSC).…”
Section: Introductionmentioning
confidence: 99%
“…Formation damage is also caused by payzone invasion from fines plugging, clay swelling, commingling of incompatible fluids, movement of dislodged formation pore-filling particles, changes in reservoirrock wettability, and formation of emulsions (Azari and Leimkuhler 1990).…”
Section: Literature Surveymentioning
confidence: 99%
“…Several studies indicated that water shock occurs only when the salt concentration in fresh water decreases below a critical salt concentration (CSC), which depends on the characteristics of the rock and the salt involved. In other words, if the formation is saturated initially with brine having salinity above CSC, and the new injected water has salinity value below CSC, clays fines migration occurs (Azari et al, 1990); however, if the initial brine has salinity below CSC, then changing salt concentration of permeating fluid will not trigger fines migration.…”
Section: Fines Migrationmentioning
confidence: 99%